Assays to Study Enzymatic and Non‐Enzymatic Protein Lysine Acetylation In Vitro. Issue 11 (8th November 2021) - Graf, Leonie G.; Vogt, Robert; Blasl, Anna‐Theresa; Qin, Chuan; Schulze, Sabrina; Zühlke, Daniela; Sievers, Susanne; Lammers, Michael
Abstract: Proteins can be lysine‐acetylated both enzymatically, by lysine acetyltransferases (KATs), and non‐enzymatically, by acetyl‐CoA and/or acetyl‐phosphate. Such modification can be reversed by lysine deacetylases classified as NAD + ‐dependent sirtuins or by classical Zn 2+ ‐dependent deacetylases (KDACs). The regulation of protein lysine acetylation events by KATs and sirtuins/KDACs, or by non‐enzymatic processes, is often assessed only indirectly by mass spectrometry or by mutational studies in cells. Mutational approaches to study lysine acetylation are limited, as these often poorly mimic lysine acetylation. Here, we describe protocols to assess the direct regulation of protein lysine acetylation by both sirtuins/KDACs and KATs, as well as non‐enzymatically. We first describe a protocol for the production of site‐specific lysine‐acetylated proteins using a synthetic biological approach, the genetic code expansion concept (GCEC). These natively folded, lysine‐acetylated proteins can then be used as direct substrates for sirtuins and KDACs. This approach addresses various limitations encountered with other methods. First, results from sirtuin/KDAC‐catalyzed deacetylation assays obtained using acetylated peptides as substrates can vary considerably compared to experiments using natively folded substrate proteins. In addition, producing lysine‐acetylated proteins for deacetylation assays by using recombinantly expressed KATs is difficult, as these often do not yield proteins that are homogeneously and quantitatively lysine acetylated. Moreover, KATs are often huge multi‐domain proteins, which are difficult to recombinantly express and purify in soluble form. We also describe protocols to study the direct regulation of protein lysine acetylation, both enzymatically, by sirtuins/KDACs and KATs, and non‐enzymatically, by acetyl‐CoA and/or acetyl‐phosphate. The latter protocol also includes a section that explains how specific lysine acetylation sites can be detected by liquid chromatography coupled to tandem mass spectrometry (LC‐MS/MS). The protocols described here can be useful for providing a more detailed understanding of the enzymatic and non‐enzymatic regulation of lysine acetylation sites, an important aspect to judge their physiological significance. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Preparation of N‐(ε)‐lysine‐acetylated proteins using the genetic code expansion concept (GCEC) Basic Protocol 2 : In vitro sirtuin (SIRT)‐catalyzed deacetylation of lysine‐acetylated proteins prepared by the GCEC Basic Protocol 3 : In vitro KDAC/HDAC‐catalyzed deacetylation of lysine‐acetylated proteins Basic Protocol 4 : In vitro lysine acetylation of recombinantly expressed proteins by lysine acetyltransferases (KATs) Basic Protocol 5 : In vitro non‐enzymatic lysine acetylation of proteins by acetyl‐CoA and/or acetyl‐phosphate